ACADEMIC PROFESSION AND IDEOLOGY OF "SLOW SCHOLARSHIP" - Roman N. Abramov; Ivan A. Gruzdev; Evgeniy A. Terent'ev (Высшее образование в России, 2016)
The article touches upon the concept of slow scholarship that has been widely spread among academic professionals abroad due to the higher education reform oriented to ideas of new managerialism. The call for slow scholarship is a reaction that faculty shows against transformation of their time budgets and weakening of professional freedom. We present a brief review of key writings on slow scholarship and discuss how these ideas can be adopted to the local context. We also reveal that research of academic profession in Russia pays relatively little attention to the issue of working time budgets and time use, while it is of a major importance to understand the changes that take place at universities and other academic institutions.